2014
DOI: 10.1155/2014/294683
|View full text |Cite
|
Sign up to set email alerts
|

Location and Roles of Deep Pools in Likangala River during 2012 Recession Period of Lake Chilwa Basin

Abstract: The ecological study focusing on Likangala River was conducted during the recent (2012) Lake Chilwa recession and aimed at identifying the important pools and the impact of indigenous ecological knowledge on the use and management of the aquatic biodiversity in the pools. An extensive georeferencing of the pools, field observations, and measurement of the pool depths was conducted to locate and map the deep pools along the river. Garmin Etrex Venture HC, GPS, and georeferencing were used to obtain the points a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
3
12
0
Order By: Relevance
“…Similarly, Limuwa et al (23) showed that fishing (90%), farming (6%), and operating small business (4%) were the main livelihood sources among communities in the Western Shore of Lake Malawi. Makwinja [16] had similar observation in Nkhotakota, Malawi. Government of Malawi report also indicates that communities in the Western Shore of Lake Malawi are predominately fishers [95].…”
Section: Characteristics Of the Respondentssupporting
confidence: 69%
“…Similarly, Limuwa et al (23) showed that fishing (90%), farming (6%), and operating small business (4%) were the main livelihood sources among communities in the Western Shore of Lake Malawi. Makwinja [16] had similar observation in Nkhotakota, Malawi. Government of Malawi report also indicates that communities in the Western Shore of Lake Malawi are predominately fishers [95].…”
Section: Characteristics Of the Respondentssupporting
confidence: 69%
“…In Lake Nasser, Egypt, the time series of size and CPUE also showed a negative trend indicating the high exploitation rate of the most important commercial fish species in the lake by the fishing gears [32]. A similar situation is reported in Lake Chilwa, Lake Malawi, and other inland lakes [35][36][37]. The option to model both fishery landings and CPUE was based on the fact that these two indicators can be used by regulators to monitor for a potential change in fish population related to the effects of human exploitation and other anthropogenic factors [38].…”
Section: Discussionsupporting
confidence: 56%
“…Dulanya et al (2014) also noted that Lake Malombe had experienced a catastrophic decline in fish stocks. Researchers such as Makwinja et al (2014) and Xu et al (2020) pointed out that the decline in fish production is highly linked to the fishery's overdependence. Similar findings have been reported in inland lakes and wetlands in Malawi and tropical regions (Kafumbata et al, 2014;Kosamu et al, 2017;Njiru et al, 2010).…”
Section: Trade-offs Between Ecosystem Servicesmentioning
confidence: 99%
“…Catchment degradation due to the vast expansion of settlements, and agricultural production instigated by high rate (2.3%) of human population growth, progressively ground cover removal, socio-economic development, and climate change has been linked to ESs erosion, particularly in tropical inland shallow lakes (Aneseyee et al, 2020;Davivongs et al, 2012;Ewunetu et al, 2021;Gondwe et al, 2019;Nkwanda et al, 2021;NSO, 2018;Seutloali & Beckedahl, 2015). Many researchers such as Lambin and Geist (2006), Sharma et al (2011), and Makwinja et al (2014) have also acknowledged that LULCDs affect ES functioning and human livelihoods through a reduction in water supply, reservoir storage capacity, agricultural productivity, and world-ecology. Vallet et al (2018) also documented that a high rate of land conversion to satisfy the demand for food production has increased pressure on ESs.…”
Section: Introductionmentioning
confidence: 99%